Detección de las prescripciones potencialmente inapropiadas según los criterios STOPP/START en pacientes ambulatorios de un hospital de la seguridad social - Patricia Guadalupe Acosta Recalde; Gladys Mabel Maidana de Larroza; Olga Yolanda Maciel de Segovia; Gladys Beatriz Lugo Rodriguez; Lourdes Raquel Samaniego Silva (Federal Council of Pharmacy, 2023)
As we age, structural and functional changes in organs occur, a process associated with multiple comorbidities requiring continuous treatment and multiple medications. Inappropriate prescription in older adults is one of the leading causes of adverse drug reactions (ADRs), associated with increased morbidity and mortality and the use of health resources. The objective of this study was to establish the frequency of potentially inappropriate prescriptions (PPI) using the STOPP/START criteria in older adult patients from the outpatient service of a Social Security Hospital through an observational, descriptive, cross-sectional, and retrospective study during the first quarter of 2021. A total of 354 prescriptions from older adult outpatients (65 years and over), of both sexes, with data collection registered in the Integrated Hospital System (SIH), were analyzed. Demographic variables were considered, including frequency of PPI according to STOPP/START criteria, where the majority of the study population were women (61.6%) with a mean age of 74 years (SD= 7.06). Of the total number of patients whose prescriptions were part of the study, 57.06% (95% CI 57.14-56.97) presented at least 1 STOPP or START criterion. The criteria applied are a helpful tool in detecting possible problems related to prescription medications, which improve the safety of older adult patients in their pharmacological treatment when used in clinical practice.